Changing epidemiologic patterns of typhus group rickettsiosis and scrub typhus in China, 1950-2022 - Ling Han; Yunfei Zhang; Xiaojing Jin; Hongyu Ren; Zhongqiu Teng; Zhaobin Sun; Jianguo Xu; Tian Qin (International Journal of Infectious Diseases, 2024)
Objectives: We conducted a systematic analysis of the notifiable rickettsial diseases in humans in China during 1950-2022. Methods: We utilized descriptive statistics to analyze the epidemiological characteristics, clinical manifestations, and diagnostic characteristics of typhus group rickettsiosis (TGR) and scrub typhus (ST) cases. Results: Since the 1950s, there have been variations in the incidence rate of TGR and ST in China, with a downtrend for TGR and an uptrend for ST. The South became a high-incidence area of TGR, whereas the North was previously the high-incidence area. ST cases were concentrated in the South and the geographic area of ST spread northward and westward. The seasonality of TGR and ST were similar in the South but distinct in the North. Most TGR and ST cases were reported by county-level medical institutions, whereas primary institutions reported the least. Delayed diagnosis was associated with fatal outcomes of TGR and ST. Cases in low-incidence provinces, confirmed by laboratory tests and reported from county/municipal-level institutions had higher odds of delayed diagnoses. Conclusions: Our study revealed significant changes in the epidemiological characteristics of TGR and ST in China, which can provide useful information to enhance the control and prevention strategies of rickettsial diseases in China.